The MOGBA randomized controlled trial: Evaluation of a complex movement skill intervention for 8–12 year old children in primary school Physical Education - Tom van Rossum; Andrew Miller; James Rudd; Johann Issartel; Jacquline D. Goodway; Donna O’Connor; Jonathan Foulkes; Jennifer Kavanagh; David Morley (PLoS ONE, 2025)
A global decline in levels of movement competence and physical activity in children presents the urgent need to look at how to reverse this trend. The Movement Oriented Games Based Assessment (MOGBA) is an intervention designed to improve children’s complex movement skills, based on principles of motor development and assessment theories. There is a positive relationship between children’s movement competence and physical activity (PA), with a further relationship established between PA and childhood obesity. This study aimed to assess how using MOGBA in PE lessons might impact primary children’s movement competence, PA, muscular fitness and self-perceptions of game and physical competence. A cluster randomized controlled trial (RCT) was conducted involving 229 children (51% girls) from nine different schools located in the north of England. The average age of participants was 9.1 years (SD = 0.21). Participants were randomized at the school level into either the MOGBA intervention group (n = 128 students) or a wait-list control group (n = 101). The MOGBA intervention was delivered over nine weeks during PE lessons by trained deliverers. The main components of the intervention included the implementation of 14 games-based activities, which were designed to support assessment within PE lessons and enhance children’s movement competence. The game-based cards also provided guidance on how to tailor activities to meet the children’s individual needs by manipulating space, effort and relationships. Pre-Post test design was employed, with participants being assessed at baseline and within 7 days post intervention. The assessment included measures of movement competence (Dragon Challenge), in-class PA (accelerometer), muscular fitness (standing long jump and plank), and perceived game and self competence (Game Play Perception Profile and Perceived Competence and Social Acceptance for Young Children). Findings show that MOGBA had a positive effect on the primary outcome of movement competence (ES: 0.18; 95%CI: −0.02, 0.38; p = 0.071) and a significant positive outcome (ES: 0.30; 95%CI: 0.04, 0.56; p = 0.025) on the way that students perceived their ability in game play. An impact was not observed on in-class PA and muscular fitness. These findings are significant as we know that increased movement competence and game self-perceptions mean children are more likely to engage with future movement, sport and physical activity opportunities. This could positively influence lifelong PA levels and promote better health. Further work should involve teachers and coaches using MOGBA to support children’s movement competence in the hopes of supporting their involvement in sport and PA. The trial is registered at the Australia New Zealand Clinical Trial Registry (ACTRN12619001320145p, 27 Sep 2019).